PENGELOLAAN DAN PEMBAGIAN SISA HASIL USAHA (SHU) KOPERASI JASA BERKAH BERSAMA SYARI’AH MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2012 - Anwar Junaidi; Dharma Setiawan; Rahmad Akbar (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study aims to determine the management and distribution of profits as the results of business activities at Jasa Berkah Bersama Syari'ah Cooperative according to the Law Number 17 of 2012. This type of research was as a qualitative approach with the research population were all administrators and members of administrators, 3 employees, 5 members. Based on the results of research, the Management and distribution profits of Jasa Berkah Bersama Syari’ah Cooperative according to Law Number 17 of 2012, can be sum up that this has complied with the provisions of Law Number 17 of 2012 as within the Management of UJKS is separated from other units in the cooperative, the cooperative management appoints the manager, management did not double as law, such as profit points that have not been used to be distributed to members in a balanced manner and managers who still have family relations.Keywords: Management, Distribution of Business Profits, Cooperative